1993
DOI: 10.1002/ajim.4700230406
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanics of vibration and low back pain

Abstract: This work is a review of the mechanical factors related to low back pain production in a vibration environment. The sitting posture is an extreme orientation for the lumbar intervertebral disc that 1) increases its internal pressure, 2) increases its anteroposterior shear flexibility, while: 3) decreasing its resistance to buckling instability and 4) stressing the posterior region of the disc. Vibration is an additional mechanical stressor. Several studies suggest that the following preventive measures be take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 50 publications
2
28
0
1
Order By: Relevance
“…The main one is that fluid flow causes variations in volume [2, 7,21] and in the mechanical properties of the disc [23]. Maintaining hydration during the experiments is therefore important [1,3,16,24].…”
Section: Mechanical Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…The main one is that fluid flow causes variations in volume [2, 7,21] and in the mechanical properties of the disc [23]. Maintaining hydration during the experiments is therefore important [1,3,16,24].…”
Section: Mechanical Testingmentioning
confidence: 99%
“…They are linked to lifestyle and in particular to the widespread operation of automobiles [3, 18,24], heavy industrial machinery and buses, and to the effort involved in lifting [9]. Many authors have studied back complaints, and have foregrounded the influence of vibrations [7] as a source of these complaints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As evidenced by cadaver experiments, mechanical damage and interference with tissue nutrition may lead to degeneration and microfractures of the vertebral endplates, increased intradiscal pressure, and rupture of disc fibres [66,67], with resultant development disc herniation [68,69]. Additionally, electromyographic studies have shown than WBV can induce fatigue in the paravertebral muscles of the lower back [65]. Thus, a degree of biological plausibility exists for a causal relationship between WBV and low back complaints, assuming that fatigue is a cause of back discomfort.…”
Section: Pathophysiology Of Wbv-related Lumbar Disordersmentioning
confidence: 99%
“…When WBV is measured on vehicle seating, it tends to show peaks of acceleration at frequencies of 2-6 Hz, which corresponds to the resonant frequency of the lumbar spine in a seated subject exposed to vertical vibration [64,65]. It is thought that such resonance can cause large relative displacements between the lumbar vertebrae, with extra compressive load and shear stress on tissues of the spine.…”
Section: Pathophysiology Of Wbv-related Lumbar Disordersmentioning
confidence: 99%